Gaussian process model for the local stellar velocity field from Gaia data release 2. Issue 4 (14th September 2022) - Nelson, Patrick; Widrow, Lawrence M
ABSTRACT: We model the local stellar velocity field using position and velocity measurements for 4M stars from the second data release of Gaia . We determine the components of the mean or bulk velocity in 27 000 spatially defined bins. Our assumption is that these quantities constitute a Gaussian process where the correlation between the bulk velocity at different locations is described by a simple covariance function or kernel. We use a sparse Gaussian process algorithm based on inducing points to construct a non-parametric, smooth, and differentiable model for the underlying mean stellar velocity field. We estimate the Oort constants A, B, C, and K and find values in excellent agreement with previous results. Maps of the velocity field within 2 kpc of the Sun reveal complicated substructures, which provide clear evidence that the local disc is in a state of disequilibrium. We present the first three-dimensional map of the divergence of the stellar velocity field and identify regions of the disc that may be undergoing compression and rarefaction.